Seasonal Patterns: Bovine Trypanosomosis, Glossina pallidipes Density, and Infection in Rift Valleys of Gamo Zone, Southern Ethiopia - Seyoum, Wasihun; Tora, Ephrem; Kore, Kokeb; Lejebo, Firew (Frontiers in Veterinary Science, 2022)
Bovine trypanosomosis is a parasitic disease causing serious economic losses in livestock productivity and agricultural development. The disease has been reported in different parts of Ethiopia. However, temporal information of trypanosomosis, tsetse fly apparent density and infection is very limited in the Southern rift valley of the country, particularly in Gamo Zone. Therefore, the objective of this cross-sectional study was to estimate seasonal prevalence of bovine trypanosomosis, assessing tsetse fly apparent density and its infection by trypanosome. For the parasitological study, a total of 600 cattle (300 in each season) were sampled and assayed using the buffy coat technique. For the entomological survey, a total of 80 standard NGU traps were deployed around the watering and grazing areas. The overall prevalence of trypanosomosis was 10.17%, of which 7.33% and 13% accounted to dry and wet seasons, respectively. The prevalence of trypanosomosis was significantly higher during wet season (OR=2.47; P< 0.05), in black coat color (OR=7.2, P< 0.05) and poor body conditioned (OR= 3.15; P< 0.05) animals. Two species of Trypanosome, T. congolense (68.85%) and T. vivax (31.15%) were circulating in the area. The mean PCV value in infected animals (22.56±4.61) was significantly lower than non-infected animals (25.3±4.75). Entomological result indicated that Glossina pallidipes (G. pallidipes) was the only species of tsetse found in the study area. Totally, 3789 flies were caught of which 81.42% belongs to G .pallidipes and 18.58% were other biting flies. The overall apparent density of G. pallidipes was 12.85 Flies/Trap/Day (FTD). Relatively higher G. pallidipes/Trap/Day caught in wet season (13.64 F/T/D) than dry season (12.07F/T/D). Of the flies caught, 342 G. pallidipes were randomly selected and dissected. The overall proportion of G. pallidipes infection was 18.42 % of which 12.28% and 24.56% accounted in dry and wet seasons, respectively. Infection in G. pallidipes was significantly higher during wet season (OR=2.32; p< 0.05) and in park grazing areas (OR= 2.45; P < 0.05). In conclusion, trypanosomosis is the major challenge for cattle productivity in the district. So this study warrants the need for strengthening the vector and parasite control interventions in the area.